Train like a mother : how to get across any finish line --and not lose your family, job, or sanity - McDowell, Dimity (Andrews McMeel Pub., 2012)
At its core, Train Like a Mother will comprehensively cover how to train for a race, including training plans for four race distances (5K, 10K, half-marathon, and marathon) for both beginner and more experienced runners; the importance of recovery; pre- and post-race nutrition; strength training; injury prevention (and rehab); and everything busy women need to know to add racing to their multitasking schedules. It is all presented with the same wit, empathy, and tone the avid fans connect and identify with. --Publisher.